Comparative Study Of Vehicle Noise Levels at Different Times In An Urban Area: A Case Study - Hasan, Indra; Albafery; Mulyadi, Agus (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Urban areas are increasingly facing the problem of noise pollution, which can significantly affect their residents' quality of life, health, and productivity. Noise caused by road traffic is one of the main contributors to this issue, particularly in cities with high traffic volumes. Despite its impact, the relationship between traffic patterns and noise levels at different times of the day remains underexplored. This study aims to investigate the variation in vehicle noise levels at different times of the day on Jalan Jenderal Sudirman in Pekanbaru City, Indonesia. The primary objective is to assess how vehicles' volume and speed contribute to noise pollution changes during peak and off-peak hours. The study was conducted by measuring the noise levels at three distinct time intervals: 07:00-09:00 GMT (morning), 11:00-13:00 GMT (daytime), and 15:00-18:00 GMT (afternoon/evening). These periods were selected to reflect the variation in traffic density and activity during the day. The data were analyzed using the ANOVA test to determine whether there were any significant differences in the noise levels across the different time intervals. The results showed that the average noise levels were similar during all three periods, with no statistically significant differences detected. The findings suggest that traffic volume and vehicle speed consistently impact noise pollution throughout the day. This study highlights the importance of managing traffic flow and vehicle speed to mitigate noise pollution in urban environments. The results also provide valuable insights for local authorities to develop policies to reduce noise pollution and improve the overall quality of life for residents in Pekanbaru.